Unique plant community with Osmorhiza aristata Rafin. in ecosystems of ribbon pine forests in the south of Western Siberia - Ovcharova, Natalia; Terekhina, Tatiana; Elesova, Natalia (Zenodo, 2023)
The article presents the results of a geobotanical study of the plant communities with the participation of a relic species Osmorhiza aristata Rafin. on the territory of the Barnaul Ribbon Forest (Altai Krai). The study of Osmorhiza aristata population was carried out during three growing seasons of 2019–2021. The phytocoenotic relationship in the conditions of habitats in Siberia, morphological characters, and origin were determined, which make it possible to suggest the natural origin of the species in the territory of the hemiboreal lowland forests in the south of Western Siberia. We determined the species composition of the forest communities in the areas of Osmorhiza aristata growth. In these communities, the number of higher vascular plants totals 30 species. The habitat characteristics of Osmorhiza aristata in the ribbon pine forests were identified. The species under consideration is included in the Red Data Book of Altai Krai (2016), the Red Data Book of the Altai Republic (2007), the Red Data Book of Kuzbass (2021), as well as in the Red Data Book of the Russian Federation (2008). Before 2019, there were four growing areas of Osmorhiza aristata known in the spruce-fir forests of Western Altai. The species was not found in the lowland part of the region. We established a new locality of the stenotopic species Osmorhiza aristata , which is not characteristic of the local flora, in the territory of Western Siberia. This study was supported by the Altai State University research grant "Monitoring phytoinvasions of Altai Krai to develop a regional approach to predicting the occurrence and dispersal of invasive species"